EFEKTIFITAS MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI KELAS VI SD NEGERI 040539 SEBERAYA SEMESTER II T.P. 2021/2022 - Erlina Br Sembiring (Jurnal Ilmu Pendidikan dan Sosial, 2022)
This study aims to improve students' understanding of learning materials and improve student learning outcomes and student learning activities by applying think pair share cooperative learning model. The subjects in this study were sixth grade students of SD Negeri 040539 Seberaya with a total of 15 students. The results of the study are: 1) Student learning outcomes by applying the TPS type cooperative learning model in the first cycle showed 6 students completed individually, while the class was incomplete. In the second cycle, 13 students completed individually and the class completed classically with an average of 66.67 and 81.33 in the first cycle and the second cycle with the percentage of classical completeness 40% in the first cycle and 87% in the second cycle. Student affective data according to observer observations in cycles I and II include: honesty from (33%) rose to (66%), discipline from (36%) rose to (73%), responsibility from (34%) rose to ( 73%), accuracy from (34%) increased to (70%), and cooperation from (30%) increased to (74%). Psychomotor data of students according to observations in cycle I and cycle II include: identifying the intent of the conversation (23%) increasing to (68%), using proper grammar (33%) increasing to (75%), speaking clearly and easy to understand (24%) increased to (70%), using the right vocabulary choices (34%) rose to (73%), and the intonation of voice according to what was conveyed (24%) rose to (60%). Completeness that occurred in cycle I and cycle II was clearly seen in class VI students when student learning was active and students understood the material presented by the researcher.